UNDERGRADUATE STUDENTS’ MOTIVES ON BACKGROUND MEDIA USE AND ITS EFFECTS READING COMPREHENSION : A CASE STUDY ON MEDIA MULTITASKING - Lo, Yong En (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study investigated students’ motivations for media multitask while studying and the effects of the presence of different forms of background media on students’ reading comprehension performance by adapting the case study design. This study had adopted the purposive sampling method to recruit 4 undergraduate students from UNIMAS who have the habit of studying with the presence of background media and have Band 4 and above for their MUET as participants. Students’ motivations to study along with background media were determined through interviews. Besides, the present study also examined if the presence of background media affects reading comprehension performance and how different forms of background media affects reading comprehension performance. Participants were tested on their reading comprehension performance under 4 conditions: lyrical music, non-lyrical music, video, and silence conditions. The findings from the interview show that there are 5 motivations why students prefer to study with background media, which are habit, boredom alleviation, prevent distraction, satisfy emotional needs, and relieve tiredness. Moreover, the findings show that the presence of background media impaired reading comprehension performance. Playing videos in the background affected the reading comprehension performance the most; the performance of the participant in lyrical music condition was slightly worse than the participant in non-lyrical music condition. The findings imply that it is important to select carefully the form of background media to combine with studying tasks.